Conversion in missionary Christianity, Northwest Tanzania : a critical assessment of methods and their impact on Haya Christian life - Rweyemamu, Josephat Alphonce (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.